2018
DOI: 10.20944/preprints201805.0311.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phytochemical Properties and Heavy Metal Contents of Commonly Consumed Alcoholic Beverages Flavoured with Herbal Extract in Nigeria

Abstract: 15There is proliferation of alcoholic beverages flavoured with herbal-extracts perceived 16 to have medicinal values. Information on the phytochemical and heavy metal 17 contents of these products is scarce. This study assessed the phytochemical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 29 publications
2
2
1
Order By: Relevance
“…The concentrations of zinc ranged between 7.638-770.797, 0-128.788 and 0-305.388 μg/L in BC, NWS and PSB, respectively. The observation concurs with other studies in other countries that found only a trace or very low Zn concentrations in alcoholic beverages (Nascimento et al, 1999;Navarro et al, 2007;Iwebgue et al, 2014;Okareh et al, 2018).…”
Section: Observed Meansupporting
confidence: 92%
See 4 more Smart Citations
“…The concentrations of zinc ranged between 7.638-770.797, 0-128.788 and 0-305.388 μg/L in BC, NWS and PSB, respectively. The observation concurs with other studies in other countries that found only a trace or very low Zn concentrations in alcoholic beverages (Nascimento et al, 1999;Navarro et al, 2007;Iwebgue et al, 2014;Okareh et al, 2018).…”
Section: Observed Meansupporting
confidence: 92%
“…Cobalt concentrations in the spirits evaluated in the study varied from 'not detected' to 0.790 μg/L in BC while no Co was detected in PSB and NWS. Iwegbue et al (2014) observed Co levels ranging from 0 -0.12 μg/mL and similar Co levels have been reported in other alcoholic beverages (Alvarez et al, 2007;Amidzi et al, 2011;Woldemariam and Chandravanshi, 2011;Okareh et al (2018)). Permissible limits of 50 µg/L and 1500 µg/L (higher levels can be related with health problems) have been reported in literature for Co levels (Oladeji and Saeed, 2015).…”
Section: Observed Meansupporting
confidence: 83%
See 3 more Smart Citations